Maxillary Sinus Floor Augmentation: a Review of Selected Treatment Modalities - Thomas Starch-Jensen; Janek Dalsgaard Jensen (Stilus Optimus, 2017)
Objectives: The objective of the present study is to present the current best evidence for enhancement of the vertical alveolar bone height and oral rehabilitation of the atrophic posterior maxilla with dental implants and propose some evidence-based treatment guidelines. Material and Methods: A comprehensive review of the English literature including MEDLINE (PubMed), Embase and Cochrane Library search was conducted assessing the final implant treatment outcome after oral rehabilitation of the atrophic posterior maxilla with dental implants. No year of publication restriction was applied. The clinical, radiological and histomorphometric outcome as well as complications are presented after maxillary sinus floor augmentation applying the lateral window technique with a graft material, maxillary sinus membrane elevation without a graft material and osteotome-mediated sinus floor elevation with or without the use of a graft material. Results: High implant survival rate and new bone formation was reported with the three treatment modalities. Perforation of the Schneiderian membrane was the most common complication, but the final implant treatment outcome was not influenced by a Schneiderian membrane perforation. Conclusions: The different surgical techniques for enhancement of the vertical alveolar bone height in the posterior part of the maxilla revealed high implant survival with a low incidence of complications. However, the indication for the various surgical techniques is not strictly equivalent and the treatment choice should be based on a careful evaluation of the individual case. Moreover, further high evidence-based and well reported long-term studies are needed before one treatment modality might be considered superior to another.